IL‐18, TNF, and IFN‐γ alleles and genotypes are associated with susceptibility to chronic hepatitis B infection and severity of liver injury. Issue 10 (7th May 2015) - Ferreira, Sandro da Costa; Chachá, Silvana Gama Florêncio; Souza, Fernanda Fernandes; Teixeira, Andreza Corrêa; de Carvalho Santana, Rodrigo; Deghaide, Neifi Hassan Saloun; Rodrigues, Sandra; Marano, Leonardo Arduíno; Mendes‐Junior, Celso Teixeira; Zucoloto, Sérgio; Donadi, Eduardo Antônio; de Lourdes Candolo Martinelli, Ana
<x xml:space="preserve">Abstract</x> Summary This study evaluated the association of polymorphisms in the IL‐18 (−607C/A and −137C/G), IFNγ (+874 A/T), and TNF (−238 A/G and −308 A/G) genes with susceptibility to HBV infection and severity of liver injury. A total of 259 chronic HBV‐infected patients followed at the University Hospital, Faculty of Medicine of Ribeirão Preto, São Paulo, Brazil, and 202 healthy individuals were studied. Four Single Nucleotide Polymorphisms (SNPs) were amplified by Polymerase Chain Reaction (PCR). Liver biopsy was performed in 212 HBV‐infected patients and classified according to severity of liver fibrosis (scores 0–4) and necroinflammatory activity (HAI scores 0–18). TNF‐308*A allele (P < 0.001; OR = 2.16) and TNF −308 AA genotype (P = 0.026; OR = 5.43) were associated with susceptibility to HBV infection. An association was found between severe liver fibrosis when compared to mild fibrosis and the following polymorphisms: Alleles IL‐18 ‐137*G (P = 0.004; OR = 3.45), TNF −308*A (P < 0.001; OR = 3.39), and IFNγ +874*T (P = 0.029; OR = 1.85) and IL‐18 −137 GG genotype (P = 0.009; OR = 3.70). No significant association was found between IL‐18 (−607 A/C) polymorphism and severity of liver fibrosis. Alleles IL‐18 −137*G (P = 0.028; OR = 2.64) and TNF‐308*A (P = 0.002; OR = 3.06) and IL‐18 −137 GG genotype (P = 0.011; OR = 4.20) were associated with severe necroinflammatory activity (HAI>12) when compared to mild necroinflammatory activity (HAI 1–8). The results suggest that IL‐18 −137C/G, TNF‐308 G/A and IFNγ +874 A/T SNPs were associated to more severe liver injury in chronic HBV infection. TNF −308*A allele and TNF −308 AA genotype could play a role in the susceptibility to HBV infection. J. Med. Virol. 87:1689–1696, 2015. © 2015 Wiley Periodicals, Inc.